Ethics, Design and Planning of the Built Environment - Basta, Claudia; Moroni, Stefano; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
The book proposes a set of original contributions in research areas shared by planning theory, architectural research, design and ethical inquiry. The contributors gathered in 2010 at the Ethics of the Built Environment seminar organized by the editors at Delft University of Technology. Both prominent and emerging scholars presented their researches in the areas of aesthetics, technological risks, planning theory and architecture. The scope of the seminar was highlighting shared lines of ethical inquiry among the themes discussed, in order to identify perspectives of innovative interdisciplinary research. After the seminar all seminar participants have elaborated their proposed contributions. Some of the most prominent international authors in the field were subsequently invited to join in with this inquiry. Claudia Basta teaches "Network Infrastructures and Mobility" at Wageningen University. Between 2009 and 2011 she worked as Coordinator of the 3TU Centre of Excellence for Ethics and Technology of Delft University, where she completed her post-doc research on the shared areas of investigation between risk theories, planning theories and ethical inquiry. Her main research interests concern the matter of assessing and governing technological risks in relation to sustainable land use planning. She wrote a number of journal articles and contributions to collective books on these themes. Stefano Moroni teaches (3z(BLand use ethics and the law(3y (Bat Milan Politecnico. His main research interests concern planning theory and ethics. He is the author of a number of books and journal articles. Recent publications (as co-author): Contractual Communities in the Self-Organizing City (Springer 2012).s
Values in planning and design: A process perspective on ethics in forming the built environment -- Architects on value: Reducing the good to the beautiful? -- A conversation about who's In? Who's out? And who answers those questions when planning for and designing the downtown? -- The relevance of public space: rethinking its material and symbolic aspects -- Incorporating ethical questions in design thinking -- Aesthetics as a risk factor in architecture -- Cost-benefit analysis and evaluating transport safety effects: A discussion from the perspective on ethics -- Urban in/justice: A literal interpretation -- Value sensitive design -- Design for meaning: a non-instrumental perspective -- Risk, space and distributive justice.-.
Keywords: Geography; Aesthetics; Ethics; Architecture; Earth Sciences; Earth Sciences, general; Cities, Countries, Regions; Ethics; Aesthetics